Identifying the Service Capability of Long-Term Care Facilities in China: An e-Delphi Study - Liu, Wen; Hu, Min; Chen, Wen (Frontiers in Public Health, 2022)
Objective This study develops a group of service capability indicators for long-term care facilities to assess their current conditions and makes it the first step toward the improvement of service capability in China. Methods We constructed an initial indicator framework based on the characteristics of long-term care services and a literature review. Potential indicators were collected, and a 2-round modified web-based Delphi process was conducted by a national multidisciplinary expert panel to construct a service capability evaluation index system. The accepted competencies of indicators were established with mean scores in all three scoring criteria (importance, feasibility, and sensitivity) ≥ 4.0, consensus rate reached 70.0%, and a coefficient of variation ≤ 0.25. Results A new indicator framework covering 2 dimensions of inputs and activities was developed in this study. The initial 35 indicators formed an indicator pool for the Delphi questionnaire. According to the final consensus of the expert panel, the Delphi consultation resulted in an index system comprised 31 tertiary indicators across six subdimensions (i) staffing; (ii) facilities and equipment; (iii) funding; (iv) medical inspection services; (v) health management services; (vi) institutional standard management. Conclusion This study developed a set of indicators suitable for the long-term care system in China and is expected to be applied to measure and improve the service capability of long-term care facilities. In addition, these indicators can be used for comparisons between different LTCFs and provide an evidence basis for the further development of capability assessment tools.